A Ruthenium‐Based Light‐Harvesting Antenna Bearing an Anthracene Moiety in Dye‐Sensitized Solar Cells. Issue 9 (14th July 2014) - Vougioukalakis, Georgios C.; Konstantakou, Maria; Pefkianakis, Eleftherios K.; Kabanakis, Antonios N.; Stergiopoulos, Thomas; Kontos, Athanassios G.; Andreopoulou, Aikaterini K.; Kallitsis, Joannis K.; Falaras, Polycarpos
Abstract A heteroleptic ruthenium sensitizer (DV56) bearing a terpyridine ligand with an appended phenylanthracene moiety was synthesized and extensively characterized. The physicochemical properties of the light‐harvesting antenna were studied in solution and on sensitized TiO2 thin film electrodes using a variety of spectroscopic and photoelectrochemical techniques. Contact angle measurements suggest that the DV56‐sensitized TiO2 films are hydrophilic. Raman measurements indicate chemisorption of the dye on the semiconducting surface. Electrochemical studies of the dye show that its first oxidation potential lies well below the I−/I3− redox potential, allowing easy regeneration. Moreover, its excited state oxidation potential lies above the TiO2 conduction band edge, permitting efficient electron injection from the photosensitizer into the semiconductor. I−/I3−‐based liquid redox electrolyte dye‐sensitized solar cells incorporating DV56‐sensitized TiO2 photoelectrodes afford an overall power conversion efficiency of 3.75 %.